Q method in research on health professions education and digital technologies: a systematic review (Research, Society and Development, 2021)
Q method, a mixed methods research approach, is used to explore points of view and attitudes towards a specific phenomenon from subjective human perspectives. There has been an increase in the use of digital technologies in education and it has become necessary to investigate the difficulties and facilities of health professionals and students in order to improve the use of such technologies for teaching and learning. We aimed to identify and evaluate studies that employed Q method to investigate the use of digital technologies in Health Professions Education. To achieve this, a systematic review was conducted according to the PRISMA Statement Guidelines. The selection of articles was based on the search strategy (("Q-sort" OR "Q-methodology" OR "Q-technique")) AND (("Teaching") OR ("Learning")). Of the 1,398 articles found, 13 were selected in accordance with the adopted inclusion criteria. The articles successfully applied Q method to health issues, which expands its application possibilities and provides a contribution to mixed methods research. Another contribution is the use of the Mixed Methods Appraisal Tool in this type of review. In view of the pressing need for education changes, using mixed methods research, particularly Q method, to investigate teaching culture and practice, can successfully support the renewal of Health Professions Education.